Synthesis And Characterizations Of Biomass-Based Graphene Metal Oxide Anodes In Microbial Fuel Cells (MFCs) Applications - Ali Yaqoob, Asim (2021)
Microbial fuel cells (MFCs) ranked among the most promising bioelectrochemical approaches for generating electrical energy while removing pollutants from wastewater, however, their relatively poor performance, has limited their commercial viability. The fabrication of advanced electrode material for MFCs is the most potential topic at present to address the issue of low electron transfer rates in the MFCs operation. In the present work, green synthesized metal oxides (ZnO and TiO2) nanoparticles (NPs) were introduced to biomass-derived graphene oxide (GO) as nanocomposite anodes. The GO/metal oxide nanocomposite anodes provide efficient energy transfer and metal ions remediation. Several toxic metals such as lead, cadmium, chromium, nickel, cobalt, and mercury were targeted in the current study.